White Matter Disease Correlates with Lexical Retrieval Deficits in Primary Progressive Aphasia - Powers, John P.; McMillan, Corey T.; Brun, Caroline C.; Yushkevich, Paul A.; Zhang, Hui; Gee, James C.; Grossman, Murray (Frontiers in Neurology, 2013)
Objective: To relate fractional anisotropy changes associated with the semantic and logopenic variants of primary progressive aphasia to measures of lexical retrieval. Methods: We collected neuropsychological testing, volumetric MRI, and diffusion-weighted imaging on semantic variant primary progressive aphasia (n=11) and logopenic variant primary progressive aphasia (n=13) patients diagnosed using published criteria. We also acquired neuroimaging data on a group of demographically comparable healthy seniors (n=34). Fractional anisotropy was calculated and analyzed using a white matter tract-specific analysis approach. This approach utilizes anatomically guided data reduction to increase sensitivity and localizes results within canonically defined tracts. We used non-parametric, cluster-based statistical analysis to relate language performance to fractional anisotropy and determine regions of reduced fractional anisotropy in patients. Results: We found widespread fractional anisotropy reductions in white matter for both variants of primary progressive aphasia. Fractional anisotropy was related to both confrontation naming and category naming fluency performance in left uncinate fasciculus and corpus callosum in semantic variant primary progressive aphasia and left superior and inferior longitudinal fasciculi in logopenic variant primary progressive aphasia. Conclusions: Semantic variant primary progressive aphasia and logopenic variant primary progressive aphasia are associated with distinct disruptions of a large-scale network implicated in lexical retrieval, and the white matter disease in each phenotype may contribute to language impairments including lexical retrieval.